The mediating role of psychological capital in health behaviors among elderly nursing home residents - Liao, Liping; Li, Yunhua; Tian, Feng; Wu, Ju; Zhong, Jing; He, Tingting; Li, Jinxiu (Frontiers in Psychology, 2025)
ObjectiveThis study aims to explore the interactions between social capital, positive psychological capital, and health-promoting behaviors among elderly residents in nursing homes in the Xiangxi region of China.MethodsA random cluster sampling method was employed to select elderly individuals from 27 nursing homes in the Xiangxi area. Data were collected using the general information questionnaire, the Social Capital Scale, the Positive Psychological Capital Scale, and the Health-Promoting Behaviors Scale. The mediating role of positive psychological capital between social capital and health-promoting behaviors was analyzed.ResultsA total of 341 questionnaires were collected from 27 nursing homes. The data reveals mean scores of 46.83 ± 10.26 for social capital, 72.48 ± 6.39 for positive psychological capital, and 68.25 ± 10.85 for health-promoting behaviors. Mediation analysis shows that the total effect of social capital on health-promoting behaviors was 0.800 (95% CI: 0.726, 0.873), with a direct effect of 0.478 (95% CI: 0.379, 0.577), accounting for 59.75% of the total effect. The indirect effect, mediated by positive psychological capital, was 0.321 (95% CI: 0.233, 0.409), contributing to 40.13% of the total effect.ConclusionPositive psychological capital acts as a mediating variable between social capital and health-promoting behaviors. Future interventions designed to enhance health-promoting behaviors must consider both social and psychological capitals to fully leverage their interplay and further promote healthy aging.